User manual for mapping Member State zoonoses standard terminology to EFSA standard terminology for information derived from the year 2018. Issue 1 (30th January 2019) - ,; Mulligan, Kenneth; Stoicescu, Anca‐Violeta
Abstract : The European Food Safety Authority (EFSA) is tasked with coordinating the reporting of zoonoses, zoonotic agents, animal populations, antimicrobial resistance and food‐borne outbreaks in the European Union (EU) under Directive 2003/99/EC, as well as analysing and summarising the data collected. For data transmission purposes, EFSA created a simple Microsoft Office Excel‐based mapping tool to allow Member States to map their standard terminology to EFSA's standard terminology. This technical report is a user manual for data providers (reporting officers and reporters) describing how to map terms and generate extensible markup language (XML) for submission of 2018 data to EFSA, according to Zoonoses data models: prevalence, antimicrobial resistance, food‐borne outbreak, animal population and disease status.